ON RECRYSTALLIZATION BEHAVIOUR IN HIGH-SPEED STEELS UNDER PULSED LASER ILLUMINATION - Andrey V. Brover; Galina I. Brover (Advanced Engineering Research)
The theoretical and experimental investigations on the development features of the structural heredity of high-speed steels under the hypernonequilibrium phase transitions are carried out. The average austenite grain diameter after different options of the volume and surface heat treatment, that permits to estimate the temperature interval of steel hardening heat, is determined.